2020
DOI: 10.3389/fpsyg.2020.534741
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an Effect of Gaming Experience on Visuospatial Attention in Deaf but Not in Hearing Individuals

Abstract: Auditory cortex in congenitally deaf early sign language users reorganizes to support cognitive processing in the visual domain. However, evidence suggests that the potential benefits of this reorganization are largely unrealized. At the same time, there is growing evidence that experience of playing computer and console games improves visual cognition, in particular visuospatial attentional processes. In the present study, we investigated in a group of deaf early signers whether those who reported recently pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Behavioral testing included visual test, Visual Puzzles as well as a set of cognitive tasks not included in this study (e.g. Holmer et al 2020 ). The behavioral testing lasted approximately 60 minutes in total.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral testing included visual test, Visual Puzzles as well as a set of cognitive tasks not included in this study (e.g. Holmer et al 2020 ). The behavioral testing lasted approximately 60 minutes in total.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that the people who are deaf have a weaker inhibitory control ability in the peripheral visual field. Similarly, Holmer et al (2020) found that deaf participants with gaming experience had better attentional control than deaf group without gaming experience, arguing that this was due to the better anti-interference ability of deaf people who played games. Therefore, weaker executive control may be the reason why the deaf adults cannot make full use of endogenous cues.…”
Section: Discussionmentioning
confidence: 95%
“…According to the literature, visuospatial attention is altered by early deafness but, interestingly, research about the gaming experience with DHH adults has proven that training visual peripherical responses in gaming (videogames) have an important role in the achievement of better visuospatial attention control, that is, the type of response to gaming challenges might contribute to minor potential visuospatial distractions. However, in our online class, which strongly differs from a traditional classroom context, we acknowledge the inherent problems of the distribution of visual attention, since all the information conveyed was relevant, contrary to the studied effect of the video game experience, which manages to train visuospatial attention by a combination of relevant-irrelevant visual stimuli using Flanker tasks 42 .…”
Section: Discussionmentioning
confidence: 99%